Strategi Komunikasi Pemasaran Wisata Kesenian Gudskul Ekosistem Gudskul Ecosystem Arts Tourism Marketing Communication Strategy - Rizki Nurul Nugraha; Vickrham ShahJehan Achmad (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the potential and development of fine arts and literature tourism objects, in this study the authors used data collection, observation, and interview methods, this research method was descriptive and qualitative techniques. The results of the study show that the Gudskul Ecosystem is a tourist attraction that has its own charm, with the attraction and potential of many local tourists and tourists who come to visit. With the marketing and development efforts carried out by Gudskul, the ecosystem will be better known by the wider community